Antiglare film, polarizing plate and display device

The anti-glare film with a structured acrylic base and coat layer addresses adhesion and mechanical issues in conventional films, providing enhanced optical and mechanical performance.

JP7618275B2Active Publication Date: 2025-01-21XINMEI HOLDINGS (HONG KONG) CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2022580507
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-07-23
Filing Date
2021-07-20
Publication Date
2025-01-21
Estimated Expiration
2041-07-20

AI Technical Summary

Technical Problem

Conventional anti-glare films using triacetyl cellulose (TAC) have low moisture permeability, and acrylic films, while improving mechanical properties, face issues with reduced adhesion and require additional primer layers, increasing cost and complexity.

Method used

An anti-glare film with a specific composition and layer structure, including an acrylic base material and a coat layer, where a monomer with a hydrophilic functional group and a polyfunctional acrylate oligomer form an intermediate layer during drying, enhancing adhesion and optical properties.

Benefits of technology

The film achieves excellent optical properties like low haze and high light transmittance, along with improved adhesion and scratch resistance, while maintaining mechanical strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007618275000003
    Figure 0007618275000003
  • Figure 0007618275000004
    Figure 0007618275000004
  • Figure 0007618275000005
    Figure 0007618275000005
Patent Text Reader

Abstract

The present invention relates to an antiglare film that includes an acrylic substrate and a coating layer located on at least one surface of the acrylic substrate, and that has a specific rate of change in band area ratio in a graph derived from the results of Raman spectroscopy analysis of the coating layer in the thickness direction, as well as a polarizing plate and a display device that include the same.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] [CROSS REFERENCE TO RELATED APPLICATIONS] This application claims the benefit of priority to Korean Patent Application No. 10-2020-0089832, filed on July 20, 2020, Korean Patent Application No. 10-2020-0089833, filed on July 20, 2020, and Korean Patent Application No. 10-2020-0091827, filed on July 23, 2020, and all contents disclosed in the documents of said Korean patent applications are incorporated herein by reference.

[0002] The present invention relates to an antiglare film, and a polarizing plate and a display device including the same. [Background technology]

[0003] As flat panel display technology develops to larger areas and higher resolutions, applicable products have expanded from home and office use such as TVs, monitors, and mobile phones to large-area displays such as outdoor billboards and electric billboards. Flat panel displays (FPDs) such as LCDs, PDPs, OLEDs, and rear-projection TVs have the problem that when exposed to external light such as natural light, the reflected light from the surface can cause eye fatigue or headaches for users, and the image created inside the display cannot be recognized as a clear image.

[0004] To solve these problems, anti-glare films are applied to scatter external light on the surface by forming unevenness on the display surface, or to induce internal scattering by using the refractive index between the resin that forms the coating layer and the particles. Conventional anti-glare films mainly use triacetyl cellulose (TAC) film as the base film, but this triacetyl cellulose film has the disadvantage of low moisture permeability.

[0005] Recently, acrylic films have been used as base films to replace triacetyl cellulose films, which have low moisture permeability. However, there is a problem that the adhesion or bonding strength between the acrylic film and the coating layer formed on the acrylic film is significantly reduced due to the stretching process to improve the mechanical properties of the acrylic film.

[0006] To solve this problem, a primer layer can be formed on the acrylic film first, and then a coating layer can be formed. However, the additional process of forming the primer layer increases costs, and it is difficult to develop a universal primer that can be applied to all base films. Summary of the Invention [Problem to be solved by the invention]

[0007] The present invention provides an anti-glare film that exhibits excellent optical properties such as low haze, high light transmittance and excellent anti-glare properties, together with improved adhesion between the substrate film and the coating layer, while also exhibiting excellent mechanical properties such as excellent scratch resistance and high hardness.

[0008] The present invention also provides a polarizing plate comprising the antiglare film.

[0009] The present invention also provides a display device including the antiglare film. [Means for solving the problem]

[0010] In the present specification, an acrylic substrate and a coating layer located on at least one surface of the acrylic substrate are included, and a graph derived from the results of performing Raman spectroscopy on the coating layer in a thickness direction from one surface of the coating layer facing the acrylic substrate shows a Raman peak of 1722 cm -1 The band area of ​​the Raman peak at 1755 cm -1The band area ratio at the graph is plotted on the Y axis, and the distance in the thickness direction from one surface of the coating layer facing the acrylic substrate is plotted on the X axis, and in the graph, the rate of change in the band area ratio according to the following formula 1 is 0.001 to 0.033 / μm. [Formula 1] Band area ratio change rate = |A2-A1| / 3 In the above formula 1, A1 is the Y value when the X value is 4 μm, A2 is the Y value when the X value is 7 μm.

[0011] In addition, in the present specification, an acrylic substrate and a coating layer located on at least one surface of the acrylic substrate are included, and a graph derived from the results of performing Raman spectroscopy on the coating layer in a thickness direction from one surface of the coating layer facing the acrylic substrate shows a Raman peak of 1722 cm -1 The band area of ​​the Raman peak at 1632 cm -1 The band area ratio at the time of measurement is plotted on the Y axis, and the distance in the thickness direction from one surface of the coating layer facing the acrylic substrate is plotted on the X axis, and in the graph, the rate of change in the band area ratio according to the following formula 2 is 0.001 to 0.050 / μm. [Formula 2] Band area ratio change rate = |A4-A3| / 3 In the above formula 2, A3 is the Y value when the X value is 4 μm, A4 is the Y value when the X value is 7 μm.

[0012] Further, the present specification provides a polarizing plate including the antiglare film.

[0013] Also provided herein is a display device comprising the antiglare film.

[0014] Hereinafter, an antiglare film according to a specific embodiment of the invention, and a polarizing plate and a display device including the same will be described in more detail.

[0015] As used herein, (meth)acrylate is meant to include both acrylate and methacrylate.

[0016] In this specification, the photopolymerizable functional group is a general term for a functional group that undergoes a polymerization reaction when irradiated with light, for example, visible light or ultraviolet light.

[0017] In addition, in this specification, the weight average molecular weight means a weight average molecular weight in terms of polystyrene measured by the GPC method. In the process of measuring the weight average molecular weight in terms of polystyrene measured by the GPC method, a commonly known analyzer, a detector such as a refractive index detector, and an analytical column can be used, and commonly applied temperature conditions, solvents, and flow rates can be applied. Specific examples of the measurement conditions include using a Polymer Laboratories PLgel MIX-B 300 mm long column and a Waters PL-GPC220 instrument, the evaluation temperature is 160° C., 1,2,4-trichlorobenzene is used as a solvent, the flow rate is 1 mL / min, and the sample is prepared to a concentration of 10 mg / 10 mL and then supplied in an amount of 200 μL, and the Mw value can be obtained using a calibration curve formed using a polystyrene standard. Nine types of polystyrene standards with molecular weights of 2,000 / 10,000 / 30,000 / 70,000 / 200,000 / 700,000 / 2,000,000 / 4,000,000 / 10,000,000 were used.

[0018] In this specification, the particle size of the particles can be measured by SEM (scanning electron microscope) image, TEM (transmission electron microscope) image, or particle size analyzer (Malvern, Japan). Specifically, the particle size of the particles can be measured by measuring the secondary particle size by dynamic light scattering of the colloidal nano solution phase using a particle size analyzer.

[0019] According to one embodiment of the invention, an acrylic substrate and a coating layer located on at least one surface of the acrylic substrate are included, and a graph derived from the results of Raman spectroscopy performed on the coating layer in a thickness direction from one surface of the coating layer facing the acrylic substrate shows a Raman peak of 1722 cm -1 The band area of ​​the Raman peak at 1755 cm -1 An antiglare film can be provided in which the band area ratio at the graph is plotted on the Y axis and the distance in the thickness direction from one surface of the coating layer facing the acrylic substrate is plotted on the X axis, and the rate of change in the band area ratio according to the following formula 1 is 0.001 to 0.033 / μm. [Formula 1] Band area ratio change rate = |A2-A1| / 3 In the above formula 1, A1 is the Y value when the X value is 4 μm, A2 is the Y value when the X value is 7 μm.

[0020] The present inventors have confirmed that an anti-glare film comprising an acrylic substrate and a coating layer located on at least one surface of the acrylic substrate, in which the rate of change in the band area ratio according to Equation 1 is 0.001-0.033 / μm, 0.002-0.032 / μm, 0.003-0.031 / μm, 0.004-0.031 / μm, 0.005-0.031 / μm, or 0.006-0.031 / μm, exhibits excellent adhesion between the acrylic substrate and the coating layer, and also exhibits excellent optical properties such as low haze, high light transmittance, and high anti-glare properties, while also exhibiting excellent mechanical properties such as excellent scratch resistance and high hardness, thereby completing the present invention.

[0021] The Raman spectroscopic analysis is performed in the thickness direction of the coating layer based on one surface of the coating layer, for example, the surface of the coating layer facing the acrylic substrate, at a measurement interval of 0.3 to 5 μm, 0.5 to 2 μm, or 1 μm.

[0022] For example, when the measurement interval is 1 μm, one surface of the coating layer is set as the reference (0 μm), and Raman spectroscopic analysis is performed first, then Raman spectroscopic analysis is performed at a position 1 μm away from the thickness direction of the one surface of the coating layer, and then Raman spectroscopic analysis is performed at a position 2 μm away from the thickness direction of the one surface of the coating layer. After that, the Raman spectroscopic analysis is performed sequentially at 1 μm intervals in the thickness direction of the coating layer up to the other surface where the coating layer contacts the acrylic base material. Alternatively, Raman spectroscopic analysis is also performed on the acrylic base material. For example, when a coating layer is formed on one surface of the acrylic base material, Raman spectroscopic analysis is performed up to the one surface of the acrylic base material facing the coating layer.

[0023] In the graph derived by the Raman spectroscopy, the X-axis is the distance in the thickness direction from one surface of the coating layer facing the acrylic substrate, and an X value of 0 μm means one surface (surface) of the coating layer facing the acrylic substrate. In addition, the graph shows the result values ​​at measurement intervals, and for example, when the measurement interval of the Raman spectroscopy is 1 μm, the graph shows the result values ​​at 1 μm intervals on the X-axis.

[0024] In the graph, the Y axis represents the Raman peak at 1722 cm -1 The band area of ​​the Raman peak at 1755 cm -1 is the ratio of the band area in

[0025] At this time, the Raman peak at 1722 cm -1 The band area at indicates the absorption peak of the carbon-oxygen double bond contained in the entire coating layer, and the carbon-oxygen double bond may be a carbon-oxygen double bond contained in an acrylate group contained in a monomer having a hydrophilic functional group and one photocurable functional group contained in the coating layer and a polyfunctional acrylate oligomer.

[0026] The Raman peak at 1755 cm -1The band area at represents the absorption peak of the stretching vibration mode of the carbon-oxygen double bond that does not participate in curing in the residual reactant contained in the coating layer, and the larger the band area of ​​the peak, the more uncured acrylate groups are distributed in the corresponding region analyzed by Raman spectroscopy. In addition, uncured acrylate groups may be distributed relatively more in the region where acrylate groups are distributed in large amounts in the coating layer.

[0027] The coating layer included in the antiglare film according to one embodiment includes a monomer having a hydrophilic functional group and one photocurable functional group and a polyfunctional acrylate oligomer as binder components, and these undergo phase separation of the binder during drying to form an intermediate layer and an antiglare layer within the coating layer. The intermediate layer is formed between the antiglare layer and the acrylic substrate, and the acrylic substrate, intermediate layer, and antiglare layer are laminated in this order.

[0028] In addition, in the graph derived from the results of the Raman spectroscopy, the Y axis represents the Raman peak at 1722 cm -1 The band area of ​​the Raman peak at 1755 cm -1 In the case of the antiglare layer, the band area ratio analyzed within the antiglare layer does not change significantly. Also, since the antiglare layer contains a larger amount of uncured acrylate than the intermediate layer, the antiglare layer shows a relatively larger band area ratio than the intermediate layer.

[0029] In addition, the intermediate layer shows a gradient of the content distribution of the uncured acrylate group within the intermediate layer, and the content of the uncured acrylate group is highest at the interface between the antiglare layer and the intermediate layer, while the content of the uncured acrylate group decreases toward the acrylic substrate. Therefore, in the case of the intermediate layer, the band area ratio is highest at the interface between the antiglare layer and the intermediate layer, and the band area ratio gradually decreases toward the acrylic substrate, and the band area ratio is lowest at the interface between the intermediate layer and the acrylic substrate.

[0030] The above formula 1 indicates that the Raman peak 1722 cm -1 The band area of ​​the Raman peak at 1755 cm -1 When the rate of change in the band area ratio according to the formula 1 is 0.001 to 0.033 / μm, it can be confirmed that an intermediate layer of a specific thickness is formed in the coating layer. On the other hand, when the rate of change according to the formula 1 exceeds the range, an intermediate layer is not formed in the coating layer, and when it is less than the range, the intermediate layer may be formed too thick.

[0031] That is, the rate of change in the band area ratio according to the formula 1 may be 0.001 to 0.033 / μm, 0.002 to 0.032 / μm, 0.003 to 0.031 / μm, 0.004 to 0.031 / μm, 0.005 to 0.031 / μm, or 0.006 to 0.031 / μm. If the rate of change in the band area ratio is too small, the intermediate layer described below is formed too thick, and the thickness of the antiglare layer is relatively too thin, resulting in a problem of reduced mechanical properties such as scratch resistance and pencil hardness, whereas if the rate of change in the band area ratio is too large, the intermediate layer described below is not formed, resulting in a problem of low adhesion between the acrylic substrate and the coating layer.

[0032] The rate of change in the band area ratio according to Equation 1 may be due to the composition of the coating layer, for example, the binder composition such as a monomer or a polyfunctional acrylate oligomer contained in the coating layer, the content or diameter of particles dispersed in the binder, or the drying conditions of the coating layer.

[0033] According to another embodiment of the present invention, an acrylic substrate and a coating layer located on at least one surface of the acrylic substrate are included, and a graph derived from the results of performing Raman spectroscopy on the coating layer in a thickness direction from one surface of the coating layer facing the acrylic substrate shows a Raman peak of 1722 cm -1 The band area of ​​the Raman peak at 1632 cm -1An antiglare film can be provided in which the band area ratio at the graph is plotted on the Y axis and the distance in the thickness direction from one surface of the coating layer facing the acrylic substrate is plotted on the X axis, and the rate of change in the band area ratio according to the following formula 2 is 0.001 to 0.050 / μm. [Formula 2] Band area ratio change rate = |A4-A3| / 3 In the above formula 2, A3 is the Y value when the X value is 4 μm, A4 is the Y value when the X value is 7 μm.

[0034] The acrylic substrate and the coating layer located on at least one surface of the acrylic substrate are included, and the rate of change in the band area ratio according to the formula 2 is 0.001 to

[0035] In the case of an antiglare film having a thickness of 0.050 / μm, 0.002 to 0.04 / μm, 0.003 to 0.03 / μm, 0.004 to 0.028 / μm, 0.005 to 0.026 / μm or 0.006 to 0.025 / μm, the adhesion between the acrylic substrate and the coating layer is excellent, and the film exhibits excellent optical properties such as low haze, high light transmittance and high antiglare properties, while also exhibiting excellent mechanical properties such as excellent scratch resistance and high hardness.

[0036] The Raman spectroscopic analysis according to the above formula 2 is carried out by the same method and conditions as those for measuring the rate of change in the band area ratio of the above formula 1.

[0037] In the graph derived by the Raman spectroscopy, the X-axis is the distance in the thickness direction from one surface of the coating layer facing the acrylic substrate, and an X value of 0 μm means one surface (surface) of the coating layer facing the acrylic substrate. In addition, the graph shows the result values ​​at measurement intervals, and for example, when the measurement interval of the Raman spectroscopy is 1 μm, the graph shows the result values ​​at 1 μm intervals on the X-axis.

[0038] In the graph, the Y axis represents the Raman peak at 1722 cm-1 The band area of ​​the Raman peak at 1632 cm -1 is the ratio of the band area in

[0039] At this time, the Raman peak at 1722 cm -1 The band area at indicates the absorption peak of the carbon-oxygen double bond contained in the entire coating layer, and the carbon-oxygen double bond may be a carbon-oxygen double bond contained in an acrylate group contained in a monomer having a hydrophilic functional group and one photocurable functional group contained in the coating layer and a polyfunctional acrylate oligomer.

[0040] At this time, the Raman peak at 1632 cm -1 The band area at indicates the absorption peak of the stretching vibration mode of the carbon-oxygen double bond that does not participate in curing in the residual reactant contained in the coating layer, and the larger the band area of ​​the peak, the more uncured acrylate groups are distributed in the corresponding region analyzed by Raman spectroscopy.

[0041] In addition, in the graph derived from the results of the Raman spectroscopy, the Y axis represents the Raman peak at 1722 cm -1 The band area of ​​the Raman peak at 1632 cm -1 In the case of the antiglare layer, the band area ratio analyzed within the antiglare layer does not change significantly. Also, since the antiglare layer contains a larger amount of uncured acrylate than the intermediate layer, the antiglare layer shows a relatively larger band area ratio than the intermediate layer.

[0042] In addition, the intermediate layer shows a gradient of the content distribution of the uncured acrylate group within the intermediate layer, and the content of the uncured acrylate group is highest at the interface between the antiglare layer and the intermediate layer, while the content of the uncured acrylate group decreases toward the acrylic substrate. Therefore, in the case of the intermediate layer, the band area ratio is highest at the interface between the antiglare layer and the intermediate layer, and the band area ratio gradually decreases toward the acrylic substrate, and the band area ratio is lowest at the interface between the intermediate layer and the acrylic substrate.

[0043] The above formula 2 indicates that the Raman peak 1722 cm -1 The band area of ​​the Raman peak at 1632 cm -1 When the rate of change in the band area ratio according to the formula 2 is 0.001 to 0.050 / μm, it can be confirmed that an intermediate layer of a specific thickness is formed in the coating layer. On the other hand, when the rate of change according to the formula 2 exceeds the range, an intermediate layer is not formed in the coating layer, and when it is less than the range, the intermediate layer may be formed too thick.

[0044] In the antiglare film according to another embodiment, the rate of change of the band area ratio according to the formula 2 may be 0.001 to 0.050 / μm, 0.002 to 0.04 / μm, 0.003 to 0.03 / μm, 0.004 to 0.028 / μm, 0.005 to 0.026 / μm, or 0.006 to 0.025 / μm. If the rate of change of the band area ratio is too small, the intermediate layer described below is formed too thick, and the thickness of the antiglare layer is relatively too thin, resulting in a problem of reduced mechanical properties such as scratch resistance and pencil hardness, whereas if the rate of change of the band area ratio is too large, the intermediate layer described below is not formed, resulting in a problem of low adhesion between the acrylic substrate and the coating layer.

[0045] The rate of change in the band area ratio according to Equation 2 may be due to the composition of the coating layer, for example, the binder composition such as a monomer or a polyfunctional acrylate oligomer contained in the coating layer, the content or diameter of particles dispersed in the binder, or the drying conditions of the coating layer.

[0046] Fig. 1 is a schematic diagram showing a cross section of an antiglare film according to an embodiment of the present invention before and after drying. Referring to Fig. 1, the antiglare film before drying includes an acrylic substrate 10 and a coating layer 20 formed on the acrylic substrate, and the coating layer includes a mixture of a monomer 100 having a hydrophilic functional group and one photocurable functional group, a multifunctional acrylate oligomer 200, and particles 300. The particles may include organic particles and / or inorganic particles.

[0047] When a drying step is performed on such an anti-glare film before drying, phase separation occurs in the binder components (monomer 100 having a hydrophilic functional group and one photocurable functional group, and multifunctional acrylate oligomer 200) contained in the coating layer 20, forming an intermediate layer 30 and an anti-glare layer 40. The intermediate layer may contain 70% by weight or more of the total amount of the monomer having the hydrophilic functional group and one photocurable functional group, and the anti-glare layer may contain less than 30% by weight of the total amount of the monomer having the hydrophilic functional group and one photocurable functional group, the multifunctional acrylate oligomer, the organic particles, and the inorganic particles.

[0048] When the drying step is performed, the majority of the monomer having the hydrophilic functional group and one photocurable functional group in the binder component, for example, about 70% by weight or more, 80% by weight or more, or 90% by weight or more of the total amount, is unevenly distributed at the interface between the coating layer and the acrylic substrate. The intermediate layer is formed by curing or crosslinking the monomer having the hydrophilic functional group and one photocurable functional group unevenly distributed at the interface. The monomer having the hydrophilic functional group and one photocurable functional group contained in the intermediate layer is physically bonded to the acrylic substrate 10.

[0049] Therefore, the intermediate layer 30 may contain 70% by weight or more of the total amount of 100 of the monomer having the hydrophilic functional group and one photocurable functional group, and the intermediate layer is physically bonded to the acrylic substrate 10. For example, the physical bond between the intermediate layer and the acrylic substrate can be achieved by physically bonding the hydrophilic functional group and one photocurable functional group contained in the intermediate layer to the acrylic substrate.

[0050] Also, the intermediate layer 30 may contain 70% by weight or more of the total amount of 100 of the monomer having the hydrophilic functional group and one photocurable functional group, and may contain a part or none of the multifunctional acrylate oligomer contained in the coating layer. For example, the intermediate layer may contain 10% by weight or less, 5% by weight or less, 1% by weight or less, or 0.01% by weight or less of the total amount of the multifunctional acrylate oligomer contained in the coating layer. Also, the intermediate layer may not contain the multifunctional acrylate oligomer, and the antiglare layer may contain the entire multifunctional acrylate oligomer. In this case, the crosslink density of the antiglare layer may be increased, and mechanical properties such as scratch resistance and pencil hardness may be improved.

[0051] Additionally, the intermediate layer 30 may include a portion of the acrylic substrate 10 that is physically bonded to the monomer 100 having the hydrophilic functional group and one photocurable functional group. For example, the intermediate layer may include the acrylic substrate in an amount of 5% or less, 3% or less, or 1% or less of the total thickness of the acrylic substrate.

[0052] In addition, an antiglare layer 40 is formed on the intermediate layer 30, the antiglare layer 40 including the polyfunctional acrylate oligomer 200, the organic particles and the inorganic particles 300 in an amount of 30% by weight or less, 20% by weight or less, or 10% by weight or less of the total amount of 100 monomers having the hydrophilic functional group and one photocurable functional group.

[0053] As described above, the intermediate layer 30 is physically bonded to the acrylic substrate 10. In addition, the intermediate layer and the antiglare layer 40 are formed by phase separation of the binder component contained in the coating layer 20, and the intermediate layer and the antiglare layer are formed in a cross-linked state. Therefore, the antiglare film according to the embodiment including the intermediate layer can greatly improve the adhesion between the acrylic substrate and the antiglare layer. The presence or absence of the intermediate layer can be confirmed by Raman spectroscopy. In the above graph, when the rate of change in the band area ratio according to the formula 1 is 0.001 to 0.033 / μm and the rate of change in the band area ratio according to the formula 2 is 0.001 to 0.050 / μm, the intermediate layer is present.

[0054] The thickness ratio of the intermediate layer 30 to the antiglare layer 40 may be 7:3 to 3:7, 6.5:3.5 to 3.5:6.5, or 6.2:3.8 to 4:6. If the thickness of the antiglare layer is too thin compared to the intermediate layer, there is a problem of reduced hardness and scratch resistance, and if the thickness of the antiglare layer is too thick compared to the intermediate layer, there is a problem of reduced adhesion due to reduced physical bonding between the substrate and the coating layer.

[0055] The thickness of the coating layer 20 including the intermediate layer 30 and the antiglare layer 40 may be 1 to 10 μm, 1.5 to 9 μm, or 2 to 8 μm. If the thickness of the coating layer is less than 1 μm, it is difficult to obtain a desired hardness, and if the thickness exceeds 10 μm, curling may occur during the process of curing the resin when forming the coating layer.

[0056] The intermediate layer 30 may have a thickness of 300 nm to 7 μm, 1 μm to 6 μm, 2 μm to 5 μm, or 2.5 μm to 4 μm. The antiglare layer 40 may have a thickness of 300 nm to 7 μm, 1 μm to 6 μm, 2 μm to 5 μm, or 2.5 μm to 4 μm.

[0057] As described above, the coating layer including the intermediate layer and the antiglare layer can contain a monomer having a hydrophilic functional group and one photocurable functional group, a polyfunctional acrylate oligomer, organic particles, and inorganic particles.

[0058] The weight ratio of the monomer having a hydrophilic functional group and one photocurable functional group to the polyfunctional acrylate oligomer may be 3:7 to 5:5, 3.5:6.5 to 5:5, or 4:6 to 5:5. If the weight ratio is less than 3:7, there may be a problem of reduced adhesion between the coating layer and the acrylic substrate, and if the weight ratio is more than 5:5, there may be a problem of reduced hardness and scratch resistance.

[0059] The coating layer may include a monomer having the hydrophilic functional group and one photocurable functional group. As described above, the coating layer includes an intermediate layer and an antiglare layer, and the intermediate layer may include 70% by weight or more, 80% by weight or more, or 90% by weight or more of the total amount of the monomer having the hydrophilic functional group and one photocurable functional group, and the antiglare layer may include less than 30% by weight, 20% by weight or less, or 10% by weight or less of the total amount of the monomer having the hydrophilic functional group and one photocurable functional group.

[0060] For example, the monomer having a hydrophilic functional group and one photocurable functional group is a compound that may contain one or more, two or more, or three or more hydrophilic functional groups and one photocurable functional group, and that is capable of forming a physical bond with the acrylic substrate.

[0061] The specific type of the hydrophilic functional group is not limited thereto, but may be one or more selected from the group including a hydroxy group, an alkoxy group, a tetrahydrofurfuryl group, and a pyrrolidone group.

[0062] The specific type of the photocurable functional group is not limited thereto, but may be at least one selected from the group consisting of a vinyl group and a (meth)acrylate group.

[0063] The specific type of the monomer having a hydrophilic functional group and one photocurable functional group is not limited to these, but may be, for example, at least one selected from the group consisting of 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-(2-ethoxyethoxy)ethyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, and N-vinylpyrrolidone.

[0064] The monomer having such a hydrophilic functional group and one photocurable functional group may be contained in an amount of 20 to 70% by weight, 30 to 60% by weight, or 35 to 55% by weight relative to 100% by weight of the coating layer (solid content). If the content of the monomer having the hydrophilic functional group and one photocurable functional group in the coating layer is too low, there is a problem of reduced adhesion between the coating layer and the acrylic substrate, and if the content of the monomer having the hydrophilic functional group and one photocurable functional group in the coating layer is too high, there is a problem of reduced hardness and scratch resistance.

[0065] The coating layer may include a polyfunctional acrylate oligomer. For example, the antiglare layer may include the polyfunctional acrylate oligomer.

[0066] The multifunctional acrylate oligomer may have a weight average molecular weight of 10,000 to 30,000, 11,000 to 27,000, or 13,000 to 25,000. If the weight average molecular weight of the multifunctional acrylate oligomer is too small, phase separation of the binder component does not occur well, resulting in a problem of reduced scratch resistance and hardness, whereas if the weight average molecular weight is too large, the bonding strength between the intermediate layer and the acrylic substrate and / or the bonding strength between the intermediate layer and the antiglare layer becomes weak, resulting in a problem of cohesive failure.

[0067] The specific types of the polyfunctional acrylate oligomer are not limited thereto, but may include, for example, one or more types selected from the group of reactive acrylate oligomers consisting of urethane acrylate oligomers, epoxy acrylate oligomers, polyester acrylates, and polyether acrylates.

[0068] The content of the multifunctional acrylate oligomer may be 20 to 80% by weight, 30 to 70% by weight, or 35 to 60% by weight based on 100% by weight of the coating layer. If the content of the multifunctional acrylate oligomer in the coating layer is too low, there is a problem of reduced hardness and scratch resistance, and if the content of the multifunctional acrylate oligomer is too high, there is a problem of reduced adhesion between the coating layer and the acrylic substrate.

[0069] The coating layer may contain organic particles and inorganic particles. For example, the antiglare layer may contain the organic particles and inorganic particles. By containing the organic particles and inorganic particles in the antiglare layer, an uneven shape is formed on one side of the antiglare layer. For example, the uneven shape is formed on one side opposite to the surface in contact with the intermediate layer.

[0070] The organic particles contained in the antiglare layer may have a diameter of 1 to 10 μm, 1.2 to 4 μm, or 1.5 to 5 μm. If the diameter of the organic particles is too small, the antiglare properties may be reduced, and if the diameter of the organic particles is too large, the unevenness may be too large, which may cause sparkling.

[0071] The organic particles have a refractive index of 1.480 to 1.620, 1.490 to 1.610, or 1.500 to 1.600 based on a wavelength of 500 to 600 nm. By including organic particles having such a high refractive index in the antiglare layer, excellent antiglare properties can be exhibited while preventing sparkling defects, lamp imaging, and light spreading.

[0072] The specific types of the organic particles are not limited thereto, but may be, for example, one selected from polystyrene, polymethyl methacrylate, polymethyl acrylate, polyacrylate, polyacrylate-co-styrene, polymethyl acrylate-co-styrene, polymethyl methacrylate-co-styrene, polycarbonate, polyvinyl chloride, polybutylene terephthalate, polyethylene terephthalate, polyamides, polyimides, polysulfone, polyphenylene oxide, polyacetal, epoxy resins, phenolic resins, silicone resins, melamine resins, benzoguanine, polydivinylbenzene, polydivinylbenzene-co-styrene, polydivinylbenzene-co-acrylate, polydiallyl phthalate, and triallyl isocyanurate polymers, or a copolymer of two or more of these may be used.

[0073] The content of such organic particles may be 0.1 to 10 wt%, 0.5 to 7 wt%, or 1 to 5 wt% relative to 100 wt% of the coating layer. If the content of the organic particles in the coating layer is too low, there is a problem of reduced antiglare properties, and if the content of the organic particles is too high, there is a problem of reduced image clarity.

[0074] The inorganic particles contained in the antiglare layer may have a diameter of 5 to 300 nm, 7 to 200 nm, or 10 to 100 nm. If the diameter of the inorganic particles is too small, there is a problem that the dispersibility is poor and unevenness may occur, and if the diameter of the inorganic particles is too large, there is a problem that it is difficult to form uniform surface unevenness.

[0075] The specific type of the inorganic particles is not limited thereto, but may be, for example, one or more types selected from the group consisting of silica, titanium dioxide, indium oxide, tin oxide, zirconium oxide, zinc oxide, and polysilsesquioxane particles (specifically, silsesquioxane particles having a cage structure).

[0076] The amount of such inorganic particles may be 0.01 to 5 wt%, 0.03 to 3 wt%, or 0.05 to 2 wt% relative to 100 wt% of the coating layer. If the amount of the inorganic particles in the coating layer is too small, unevenness is not formed, resulting in a decrease in antiglare properties. If the amount of the inorganic particles in the coating layer is too large, unevenness defects occur due to excessive aggregation.

[0077] The weight ratio of the inorganic particles to the organic particles contained in the antiglare layer may be 1:1 to 100, 1:2 to 90, or 1:5 to 80. If the weight ratio of the inorganic particles to the organic particles exceeds 1:1, image clarity may decrease or sparkling may occur, and if it is less than 1:100, the size of the uneven shape formed on the surface of the antiglare layer may become small, which may induce glare.

[0078] The organic particles and inorganic particles may have a particle shape such as a sphere, an oval sphere, a rod shape, an irregular shape, etc. In the case of a rod shape or an irregular shape, the length of the largest dimension may satisfy the particle diameter range.

[0079] The substrate film of the anti-glare film of the embodiment may be an acrylic substrate. Although such an acrylic substrate has excellent moisture permeability and transparency, it has a problem of low adhesion to a coating layer formed on the acrylic substrate. However, in the anti-glare film according to the embodiment, an intermediate layer that is physically bonded to the acrylic substrate is formed on the acrylic substrate, and an anti-glare layer that is cross-linked to the intermediate layer is formed on the intermediate layer. Therefore, such an intermediate layer can improve the adhesion and adhesion between the anti-glare layer and the acrylic substrate.

[0080] A more specific example of the acrylic substrate is, but is not limited to, an acrylic substrate containing an alkyl (meth)acrylate, for example, the alkyl (meth)acrylate being one or more selected from the group consisting of methyl acrylate, ethyl acrylate, methyl methacrylate, and ethyl methacrylate.

[0081] The acrylic resin may further contain, together with the alkyl (meth)acrylate, one or more components selected from the group consisting of (meth)acrylic acid, maleic anhydride, and maleimide.

[0082] The acrylic substrate may be biaxially stretched, and for example, the stretch ratio in the machine direction (MD) may be 1.1 to 2.5, 1.2 to 2.0, or 1.3 to 1.95. The stretch ratio in the transverse direction (TD) of the acrylic substrate may be 1.1 to 3.5, 1.2 to 3.0, or 1.3 to 2.8. When the acrylic substrate satisfies the above-mentioned stretch ratios, the film can exhibit excellent mechanical properties such as toughness.

[0083] Considering the excellent mechanical properties, water resistance, low moisture permeability, and excellent optical properties of the anti-glare film according to the embodiment, the thickness of the acrylic substrate may be, but is not limited to, 10 to 300 μm, 30 to 250 μm, or 40 to 200 μm.

[0084] The antiglare film according to the embodiment may have a light transmittance of 90.0% or more, 90.5% or more, or 91.0% or more.

[0085] The antiglare film may have a total haze of 0.5 to 10%, 0.7 to 8%, or 0.9 to 5%.

[0086] The antiglare film may have an internal haze of 0.3 to 7%, 0.7 to 5%, or 0.9 to 3%.

[0087] The intermediate layer and the antiglare layer are formed by a process of applying a resin composition for forming a coating layer, which contains a monomer having a hydrophilic functional group and one photocurable functional group, a polyfunctional acrylate oligomer, organic particles and inorganic particles, to one surface of an acrylic substrate, followed by drying and curing.

[0088] In addition, the resin composition for forming a coating layer may further include a photoinitiator. Therefore, the photoinitiator may remain in the coating layer produced from the above-mentioned resin composition for forming a coating layer. As the photoinitiator, any compound known to be usable in the resin composition for forming a coating layer may be used without any significant limitations, and specifically, benzophenone-based compounds, acetophenone-based compounds, biimidazole-based compounds, triazine-based compounds, oxime-based compounds, or mixtures of two or more of these may be used.

[0089] The photoinitiator may be used in an amount of 0.1-10 wt%, 0.5-9 wt%, or 1-8 wt% based on 100 wt% of the composition. If the amount of the photoinitiator is too small, uncured residual material may be generated during the photocuring step. If the amount of the photoinitiator is too large, unreacted initiator may remain as an impurity or the crosslinking density may be low, resulting in poor mechanical properties of the film or excessively high reflectance.

[0090] In addition, the resin composition for forming a coating layer may further include an organic solvent, non-limiting examples of which include ketones, alcohols, acetates, ethers, benzene derivatives, or a mixture of two or more of these.

[0091] Specific examples of such organic solvents include ketones such as methyl ethyl ketone, methyl isobutyl ketone, acetylacetone, or isobutyl ketone; alcohols such as methanol, ethanol, n-propanol, i-propanol, n-butanol, i-butanol, or t-butanol; acetates such as ethyl acetate, i-propyl acetate, or polyethylene glycol monomethyl ether acetate; ethers such as tetrahydrofuran or propylene glycol monomethyl ether; benzene derivatives such as toluene, xylene, or aniline; or a mixture of two or more of these.

[0092] The organic solvent may be added when each component contained in the resin composition for forming a coating layer is mixed, or each component may be added in a state of being dispersed or mixed in the organic solvent and then included in the resin composition for forming a coating layer. If the content of the organic solvent in the resin composition for forming a coating layer is too small, the flowability of the resin composition for forming a coating layer may decrease, and defects such as stripes may occur in the film finally produced. In addition, if the organic solvent is added in an excessive amount, the solid content may be low, and coating and film formation may not be performed sufficiently, and the physical properties and surface characteristics of the film may be reduced, and defects may occur during the drying and curing process. Therefore, the resin composition for forming a coating layer may contain an organic solvent so that the concentration of the total solid content of the components contained therein is 10 to 50 wt % or 15 to 40 wt %.

[0093] Meanwhile, methods and devices that are commonly used for applying the resin composition for forming the coating layer can be used without particular limitations. For example, a bar coating method such as a Meyer bar, a gravure coating method, a 2 roll reverse coating method, a vacuum slot die coating method, a 2 roll coating method, etc. can be used.

[0094] In the step of drying the resin composition for forming the coating layer, phase separation of the binder components (monomer having a hydrophilic functional group and one photocurable functional group, polyfunctional acrylate oligomer) may occur as described above. For example, 70% by weight or more of the total amount of the monomer having the hydrophilic functional group and one photocurable functional group contained in the resin composition for forming the coating layer may be physically bonded to the acrylic substrate and unevenly distributed at the interface between the acrylic substrate and the coating layer. Therefore, the monomer having the hydrophilic functional group and one photocurable functional group unevenly distributed at the interface is photocured while being physically bonded to the acrylic substrate to form an intermediate layer. Therefore, the intermediate layer can include the monomer having the hydrophilic functional group and one photocurable functional group, and a part of the acrylic substrate physically bonded to the monomer having the hydrophilic functional group and one photocurable functional group. In addition, an antiglare layer is formed on the intermediate layer, and such antiglare layer may contain less than 30 weight % of the total amount of the monomer having the hydrophilic functional group and one photocurable functional group, the polyfunctional acrylate oligomer, the organic particles, and the inorganic particles.

[0095] Such a drying step is carried out at a temperature of 60 to 100° C., 65 to 95° C., or 70 to 93° C. for 30 seconds to 30 minutes, 1 to 25 minutes, or 2 to 15 minutes.

[0096] In the photo-curing step after the drying process, ultraviolet rays or visible light having a wavelength of 200 to 400 nm may be irradiated, and the exposure dose during irradiation is 100 to 4,000 mJ / cm. 2 , 150~2,000mJ / cm 2 or 200-1,000mJ / cm 2 The exposure time is not particularly limited, and can be appropriately changed depending on the exposure device used, the wavelength of the irradiated light, or the exposure dose. In addition, in the photocuring step, nitrogen purging can be performed to apply nitrogen atmosphere conditions.

[0097] According to another embodiment of the present invention, there is provided a polarizing plate including the antiglare film. The polarizing plate may include a polarizing film and an antiglare film formed on at least one surface of the polarizing film.

[0098] The material and manufacturing method of the polarizing film are not particularly limited, and any common material and manufacturing method known in the art can be used. For example, the polarizing film can be a polyvinyl alcohol-based polarizing film.

[0099] A protective film is provided between the polarizing film and the antiglare film. Examples of the protective film are not limited, and may be at least one of a COP (cycloolefin polymer) film, an acrylic film, a TAC (triacetylcellulose) film, a COC (cycloolefin copolymer) film, a PNB (polynorbornene) film, and a PET (polyethylene terephtalate) film.

[0100] The protective film may be a substrate for forming a single coating layer when the antiglare film is manufactured. The polarizing film and the antiglare film are attached to each other by an adhesive such as a water-based adhesive or a non-water-based adhesive.

[0101] According to yet another embodiment of the invention, there is provided a display device including the antiglare film described above.

[0102] Specific examples of the display device are not limited to those mentioned above, and may be, for example, a liquid crystal display device, a plasma display device, an organic light emitting diode device, and the like.

[0103] As one example, the display device may be a liquid crystal display device including a pair of polarizing plates facing each other, a thin film transistor, a color filter, and a liquid crystal cell sequentially stacked between the pair of polarizing plates, and a backlight unit. In the display device including the antiglare film, the antiglare film may be disposed on one surface of the polarizing plate that is relatively far from the backlight unit, among the pair of polarizing plates.

[0104] In the display device, the anti-glare film is provided on the outermost surface of the viewer side or the backlight side of the display panel. More specifically, the display device may be a display device for a notebook computer, a display device for a TV, or a large-area display device for advertising, and the anti-glare film may be located on the outermost surface of the display device for a notebook computer, a display device for a TV, or a large-area display device for advertising. Effect of the Invention

[0105] According to the present invention, an anti-glare film having excellent optical properties such as low haze, high light transmittance and excellent anti-glare properties together with improved adhesion between a substrate film and a coating layer, and also having excellent mechanical properties such as excellent scratch resistance and high hardness, as well as a polarizing plate and a display device including the same can be provided. [Brief description of the drawings]

[0106] [Figure 1] 1A and 1B are schematic diagrams illustrating cross sections of an antiglare film according to one embodiment of the present invention before and after drying. [Diagram 2] 1 is a photograph of the antiglare film of Example 1 taken with an electron microscope. [Diagram 3] 1 is a graph derived from the results of Raman spectroscopy analysis of the antiglare film of Example 2 (the rate of change in band area ratio according to Equation 1). [Figure 4] 1 is a graph derived from the results of Raman spectroscopy analysis of the antiglare film of Comparative Example 1 (the rate of change in band area ratio according to Formula 1). [Diagram 5]1 is a graph derived from the results of Raman spectroscopy analysis of the antiglare film of Example 2 (the rate of change in band area ratio according to Equation 2). [Figure 6] 1 is a graph derived from the results of Raman spectroscopy analysis of the antiglare film of Comparative Example 1 (the rate of change in band area ratio according to Equation 2). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0107] The present invention will be described in more detail with reference to the following examples, however, the following examples are merely illustrative and the content of the present invention is not limited to the following examples.

[0108] (Production Example 1: Production of resin composition for forming coating layer) 50 g of tetrahydrofurfuryl acrylate, 50 g of CN9013NS (urethane-modified 9-functional acrylate oligomer, weight average molecular weight: 20,000, manufactured by Sartomer), 5 g of initiator Irgacure184 (manufactured by Ciba), 100 g of solvent methyl isobutyl ketone, 0.4 g of MA-ST (silica nanoparticles, particle size: 12 nm, 30% dispersion in methanol), and 2 g of first organic particles (polystyrene-polymethyl methacrylate copolymerized spherical organic particles, diameter: 2 μm, refractive index n=1.515) were mixed to produce a resin composition for forming a coating layer of Production Example 1.

[0109] (Production Example 2: Production of resin composition for forming coating layer) 50 g of 2-hydroxyethyl acrylate, 50 g of CN8885NS (multifunctional acrylate oligomer, weight average molecular weight: 14,000, manufacturer: Sartomer), 5 g of initiator (Irgacure184), 100 g of methyl isobutyl ketone as a solvent, 0.2 g of MA-ST, and 2 g of the first organic particles were mixed to produce a resin composition for forming a coating layer of Production Example 2.

[0110] (Production Example 3: Production of resin composition for forming coating layer) 20 g of 2-hydroxyethyl acrylate, 20 g of 4-hydroxybutyl acrylate, 60 g of CN8885NS, 5 g of initiator (Irgacure184), 100 g of methyl isobutyl ketone as a solvent, 0.3 g of MA-ST, and 2 g of second organic particles (polystyrene-polymethyl methacrylate copolymer spherical organic particles, diameter: 2 μm, refractive index n=1.555) were mixed to produce a resin composition for forming a coating layer of Production Example 3.

[0111] (Comparative Production Example 1: Production of resin composition for forming coating layer) A resin composition for forming a coating layer of Comparative Preparation Example 1 was prepared by mixing 20 g of 2-hydroxyethyl acrylate, 80 g of CN8885NS, 5 g of an initiator (Irgacure184), 100 g of methyl isobutyl ketone as a solvent, 0.7 g of MA-ST, and 4 g of the first organic particles.

[0112] (Comparative Production Example 2: Production of Resin Composition for Forming Coating Layer) A resin composition for forming a coating layer of Comparative Preparation Example 2 was prepared by mixing 50 g of pentaerythritol triacrylate (PETA), 50 g of 1,6-hexadiol diacrylate (HDDA), 5 g of an initiator (Irgacure 184), 100 g of methyl isobutyl ketone as a solvent, 0.7 g of MA-ST, and 4 g of the first organic particles.

[0113] (Examples and Comparative Examples: Production of Antiglare Film) The resin compositions for forming a coating layer of Production Examples 1 to 3 and Comparative Production Examples 1 to 2 thus obtained were coated onto an acrylic substrate (manufacturer: LG Chem, thickness: 40 μm, stretch ratio MD×TD: 1.95×1.8) using a #12 Meyer bar and dried at 90° C. for 2 minutes. The dried product was then irradiated with a mercury lamp at 200 mJ / cm 2 The thickness of the coating layer was measured using a digital micrometer and is shown in Table 1 below.

[0114] Meanwhile, the content of monomers having a hydrophilic functional group and one photocurable functional group (tetrahydrofurfuryl acrylate, 2-hydroxyethyl acrylate or 4-hydroxybutyl acrylate) relative to the total amount of the coating layer (solid content) was confirmed, and the results are shown in [Content of monofunctional monomer relative to coating layer] in Table 1 below.

[0115] [Table 1]

[0116] (1. Measurement of the rate of change in band area ratio using Equation 1 on a Raman spectrograph) Raman spectroscopic analysis was performed at 1 μm intervals in the thickness direction from the surface of the coating layer of the antiglare films of the Examples and Comparative Examples (specifically, one surface of the coating layer facing the acrylic substrate), and the analysis conditions for Raman spectroscopic analysis were as follows: For the Raman spectroscopic analysis, the samples were microtomed at a width of 1 to 2 μm.

[0117] <Raman spectroscopic analysis conditions> -Device: RAMANTouch (manufacturer: Nanophoton) -Microscope mode: 180° back scattering -Objective Lens: TU Plan Fluor 100x / NA 0.90 -Light source: Ar + Laser, wavelength 532nm -Grating: 600gr / mm -Spectral resolution: 2.1cm -1 (@532nm, 600gr / mm) -Detector: TE-cooled CCD 1340×400 pixel format

[0118] Thereafter, the Raman spectroscopy analysis results, which were analyzed at 1 μm intervals in the thickness direction, showed a Raman peak of 1722 cm-1 Band area and Raman peak at 1755 cm -1 The band area at the Raman peak 1722 cm was calculated by integration. -1 The band area of ​​the Raman peak at 1755 cm -1 The band area ratio was calculated and shown in a graph. In this graph, the X-axis corresponds to the distance from the surface of the coating layer facing the acrylic substrate in the thickness direction, and the Y-axis corresponds to the band area ratio.

[0119] FIG. 3 is a graph derived from the results of Raman spectroscopic analysis of the antiglare film of Example 2 (the rate of change in band area ratio according to Equation 1), and FIG. 4 is a graph derived from the results of Raman spectroscopic analysis of the antiglare film of Comparative Example 1 (the rate of change in band area ratio according to Equation 1).

[0120] In the above-mentioned graphs using Raman spectroscopy for the antiglare films of the Examples and Comparative Examples, the rate of change in the band area ratio was measured according to the following formula 1, and the results are shown in the following Table 2. At this time, when the rate of change in the band area ratio is 0.001 to 0.033 / μm, it means that an intermediate layer is formed in the antiglare film. [Formula 1] Band area ratio change rate = |A2-A1| / 3 In the above formula 1, A1 is the Y value when the X value is 4 μm, A2 is the Y value when the X value is 7 μm.

[0121] (2. Measurement of the rate of change in band area ratio using Equation 2 on a Raman spectrograph) The rate of change in the band area ratio according to formula 2 was measured under the same measurement conditions as in "1. Measurement of the rate of change in the band area ratio according to formula 1 in a Raman spectrograph" above.

[0122] However, in the Raman spectroscopy analysis performed at 1 μm intervals in the thickness direction, the Raman peak was 1722 cm -1Band area and Raman peak at 1632 cm -1 The band area at the Raman peak 1722 cm was calculated by integration. -1 The band area of ​​the Raman peak at 1632 cm -1 The band area ratio was calculated and shown in a graph. In this graph, the X-axis corresponds to the distance from surface of the coating layer facing the acrylic substrate in the thickness direction, and the Y-axis corresponds to the band area ratio.

[0123] FIG. 5 is a graph derived from the results of Raman spectroscopic analysis of the antiglare film of Example 2 (the rate of change in band area ratio according to Equation 2), and FIG. 6 is a graph derived from the results of Raman spectroscopic analysis of the antiglare film of Comparative Example 1 (the rate of change in band area ratio according to Equation 2).

[0124] In the above-mentioned graphs using Raman spectroscopy for the antiglare films of the Examples and Comparative Examples, the rate of change in the band area ratio was measured according to the following formula 2, and the results are shown in the following Table 2. At this time, when the rate of change in the band area ratio is 0.001 to 0.050 / μm, it means that an intermediate layer is formed in the antiglare film. [Formula 2] Band area ratio change rate = |A4-A3| / 3 In the above formula 2, A3 is the Y value when the X value is 4 μm, A4 is the Y value when the X value is 7 μm.

[0125] (3. Measurement of the thickness of the intermediate layer) The antiglare films of the examples and comparative examples were photographed with an electron microscope to measure the thickness of the intermediate layer. Fig. 2 is a photograph of the antiglare film of Example 1 taken with an electron microscope, and the thickness of the intermediate layer was measured based on this.

[0126] On the other hand, in Table 2 below, "-" corresponds to the case where the intermediate layer was not generated.

[0127] (4. Evaluation of Transmittance and Haze) A 4 cm x 4 cm test piece was prepared from the antiglare film of each of the examples and comparative examples, and the haze was measured three times using a haze measuring device (HM-150, A light source, Murakami Co., Ltd.) to calculate the average value, which was calculated as the overall haze value. At this time, the light transmittance and the overall haze were measured simultaneously, and the light transmittance was measured according to JIS K 7361 and the haze was measured according to JIS K 7136.

[0128] (5. Evaluation of Adhesion (Cross-Cut)) Based on ASTM D3359, 100 (10x10) cuts were made in the coating layer of the antiglare film of the examples and comparative examples so that the width and length were 1 mm, tape (product name: CT-24, manufacturer: Nichiban) was attached, and the number of squares of the coating layer that remained without peeling off together with the tape was counted after peeling. If the number of squares that remained without peeling off was 100% of the total squares, it was marked as 5B, if it was 95% or more but less than 100%, it was marked as 4B, if it was 85% or more but less than 95%, it was marked as 3B, if it was 65% or more but less than 85%, it was marked as 2B, if it was 35% or more but less than 65%, it was marked as 1B, and if it was 0% or more but less than 35%, it was marked as 0B.

[0129] (6. Scratch Resistance Evaluation) The coating layer of the antiglare film of the examples and comparative examples was rubbed 10 times back and forth at 30 rpm with steel wool (#0000) with a load of 500 g, and the presence or absence of scratches was checked with the naked eye. If one or less scratches of 1 cm or less were observed with the naked eye, it was judged as good, and if more than one scratch was observed, it was judged as poor.

[0130] [Table 2]

[0131] According to Table 2 above, the rate of change in the band area ratio according to the above formula 1 in Examples 1 to 3 was 0.001 to 0.033 / μm, and the rate of change in the band area ratio according to the above formula 2 was 0.001 to 0.050 / μm. It was confirmed that the films exhibited high transmittance and low haze, thus exhibiting excellent optical properties, excellent adhesion between the acrylic substrate and the coating layer, and good scratch resistance.

[0132] In addition, in Comparative Example 1 and Comparative Example 2, the monomer having a hydrophilic functional group and one photocurable functional group is contained in an excessively small amount or is not used at all, so the rate of change in the band area ratio according to the above formula 1 does not satisfy the range of 0.001 to 0.033 / μm, and the rate of change in the band area ratio according to the above formula 2 does not satisfy the range of 0.001 to 0.050 / μm, and it was confirmed that the adhesion between the acrylic substrate and the coating layer is reduced. [Explanation of symbols]

[0133] 10 Acrylic substrate 20 Coating Layer 30 Middle Class 40 Anti-glare layer 100 Monomer having a hydrophilic functional group and one photocurable functional group 200 Multifunctional acrylate oligomer 300 particles

Claims

1. The coating layer includes an acrylic substrate and a coating layer located on at least one surface of the acrylic substrate, The coating layer is formed by applying a coating layer-forming resin composition, which includes a monomer having a hydrophilic functional group and one photocurable functional group, a polyfunctional acrylate oligomer, organic particles, and inorganic particles, to one surface of the acrylic base material, and then drying and curing the composition. the content of the monomer having a hydrophilic functional group and one photocurable functional group is 20 to 70% by weight based on the total weight of the coating layer (solid content); A graph derived from the results of performing Raman spectroscopy on the coating layer in the thickness direction from one surface of the coating layer facing the acrylic base material shows a Raman peak at 1722 cm -1 Raman peak 1755 cm -1 The ratio of the band area at the band area is represented on the Y axis, and the distance in the thickness direction from one surface of the coating layer facing the acrylic base material is represented on the X axis. In the graph, the rate of change in the band area ratio according to the following formula 1 is 0.001 to 0.033 / μm. [Formula 1] Rate of change in band area ratio = |A 2 -A 1 | / 3 In the above formula 1, A 1 is the Y value when the X value is 4 μm, A 2 is the Y value when the X value is 7 μm.

2. The coating layer includes an acrylic substrate and a coating layer located on at least one surface of the acrylic substrate, The coating layer is formed by applying a coating layer-forming resin composition, which includes a monomer having a hydrophilic functional group and one photocurable functional group, a polyfunctional acrylate oligomer, organic particles, and inorganic particles, to one surface of the acrylic base material, and then drying and curing the composition. the content of the monomer having a hydrophilic functional group and one photocurable functional group is 20 to 70% by weight based on the total weight of the coating layer (solid content); A graph derived from the results of performing Raman spectroscopy on the coating layer in the thickness direction from one surface of the coating layer facing the acrylic base material shows a Raman peak at 1722 cm -1 Raman peak 1632 cm -1 The ratio of the band area at the band area is represented on the Y axis, and the distance in the thickness direction from one surface of the coating layer facing the acrylic base material is represented on the X axis. In the graph, the rate of change in the band area ratio according to the following formula 2 is 0.001 to 0.050 / μm. [Formula 2] Rate of change in band area ratio = |A 4 -A 3 | / 3 In the above formula 2, A 3 is the Y value when the X value is 4 μm, A 4 is the Y value when the X value is 7 μm.

3. The coating layer is An intermediate layer containing 70% by weight or more of the total amount of the monomer having a hydrophilic functional group and one photocurable functional group; and 3. The antiglare film according to claim 1, further comprising an antiglare layer comprising: less than 30% by weight of the total amount of the monomer having a hydrophilic functional group and one photocurable functional group, the polyfunctional acrylate oligomer, the organic particles, and the inorganic particles.

4. The antiglare film according to any one of claims 1 to 3, wherein a weight ratio of the monomer having a hydrophilic functional group and one photocurable functional group, and the polyfunctional acrylate oligomer contained in the coating layer is 3:7 to 5:

5.

5. The antiglare film of claim 3 , wherein the intermediate layer is physically bonded to the acrylic substrate.

6. The antiglare film according to claim 3 or 5, wherein the monomer having a hydrophilic functional group and one photocurable functional group contained in the intermediate layer is physically bonded to the acrylic substrate.

7. 7. The antiglare film of claim 3, 5, or 6, wherein the intermediate layer comprises a portion of the acrylic substrate physically bonded to a monomer having the hydrophilic functional group and one photocurable functional group.

8. The monomer having a hydrophilic functional group and one photocurable functional group is at least one selected from the group consisting of 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-(2-ethoxyethoxy)ethyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, and N-vinylpyrrolidone. The antiglare film according to any one of claims 1 to 7.

9. The antiglare film according to any one of claims 1 to 8, wherein the polyfunctional acrylate oligomer has a weight average molecular weight of 10,000 to 30,000.

10. The antiglare film according to claim 3, 5, 6, or 7, wherein the thickness ratio of the intermediate layer and the antiglare layer is 7:3 to 3:

7.

11. The antiglare film according to claim 3, 5, 6, 7, or 10, wherein the coating layer has a thickness of 1 to 10 μm.

12. 12. The antiglare film according to claim 3, 5, 6, 7, 10, or 11, wherein the antiglare layer has a surface formed with unevenness.

13. The antiglare film according to any one of claims 1 to 12, wherein the antiglare film has a total haze of 0.5 to 10% and an internal haze of 0.3 to 7%.

14. A polarizing plate comprising the antiglare film according to any one of claims 1 to 13.

15. A display device comprising the antiglare film according to any one of claims 1 to 13.

Citation Information

Patent Citations

  • Composition for forming optical film, optical film and polarizing plate including the same

    JP2019533186A